La Francia e una Fiat 500: i primi esperimenti di Alighiero Boetti. - Bottinelli, Silvia. (Tufts University. Tisch Library., 2017)
Alighero Boetti (1940-1994) traveled to the French Riviera and Paris regularly from 1962 to 1964. At that time, the artist was a student in Economics at the University of Turin. His interest in France was initially of commercial nature. Boetti visited ceramics studios in Antibes and Vallauris in order to purchase artisanal objects by famous modernist artists. Despite its being intended as a business, Boetti's little enterprise did not fail to expose him to the art of de Stäel. Matisse, and Yves Klein, among others. The French Riviera had long-lasting effects on Boetti's artistic memory and creativity. The artist's trips to Southern France connected him to artworks that left a mark on his visual memory and may be linked to practices that he experimented with in subsequent years, such as the accumulation of everyday materials, the artisanal seriality of crafts, and the relational exchanges enabled by travel.